Managing management information systems - Ein-Dor, Phillip; Segev, Eli. (Lexington, Mass. : Lexington Books, 1978)
This book cover the two major components of management information system. it highlights various layers of MIS such as their concepts, definitions, and characteristics.
Includes bibliographical references and index.
asm 14/02/2019
Loans
Keywords: Management information systems